A STUDY OF THE IMPACTS OF CARS EQUIPPED WITH ELASTOMERIC ABSORBING DEVICES USING COMPUTER SIMULATION - Biespalko, S. V.; Andriianov, S. S. (Science and Transport Progress, 2004)
Software to investigate the elastomer absorbing devices work at various trains collision speeds is created. A comparison of the obtained simulation results with tests shows their good agreement.